With letters of light [Be-otiyot shel or] : studies in the Dead Sea scrolls, early Jewish apocalypticism, magic and mysticism in honor of Rachel Elior - Orlov, Andrei A., 1960-; Arbel, Daphna (New York : Walter de Gruyter, 2011)
"This volume offers valuable insights into a wide range of scholarly achievements in the study of the Dead Sea Scrolls, Jewish apocalypticism, magic, and mysticism from the Second Temple period to the later rabbinic and Hekhalot developments. The majority of articles included in the volume deal with Jewish and Christian apocalyptic and mystical texts constituting the core of experiential dimension of these religious traditions"--ECIP summary.
Rachel Elior : an appreciation from her colleagues and students / Daphna Arbel and Andrei Orlov -- The consideration of religious experience in the work of Racel Elior / Frances Flannery -- Peter and the patriarch : a confluence of traditions? / Kelley Coblentz Bautch -- In heaven or on earth : a misplaced temple question about Ezekiel's visions / Silviu N. Bunta -- Scriptural exegesis in the Treatise of the Vessels, a legendary account of the hiding of the temple treasures / James R. Davila -- Cultivating visions through exegetical meditations / Dan Merkur -- "Serpentine" eve in Syriac Christian literature of late antiquity / Sergey Minov -- From "pre-emptive exegesis" to "pre-emptive speculation"? Ma'aseh Bereshit in Genesis Rabbah and Pirqei deRabbi Eliezer / Annette Yoshiko Reed -- Earthly and heavenly Jerusalem in Philo and Paul : a tale of two cities / Mark Verman -- The Book of Watchers and the cycle of new year festivals / Crispin Fletcher-Louis -- A different spirituality or 'other' agents? : on the study of magic in Rabbinic literature / Yuval Harari -- "They revealed secrets to their wives" : the transmission of magical knowledge in 1 Enoch / Rebecca Lesses -- The impurity of oil and spit among the Qumran sectarians / Jodi Magness -- "The Likeness of heaven" : the Kavod of Azazel in the Apocalypse of Abraham / Andrei Orlov -- Mystical motifs in a Greek synagogal prayer? / Pieter W. van der Horst -- "A chariot of light borne by four bright eagles" : Eve's vision of the chariot in the Greek life of Adam and Eve / Daphna Arbel -- "Messianic movements in the period of the crusades" / Joseph Dan -- Jesus revealed : the dynamics of early Christian mysticism / April D. DeConick -- Aseneth : ascetical practice, vision, and transformation / Celia Deutsch -- "You are gods" : multiple divine beings in late antique Jewish theology / Naomi Janowitz -- Transcribing experience / Alan F. Segal.
Includes bibliographical references (p. [383]-447) and index.
With occasional Greek, Hebrew and Syriac.
Description based on print version record.
Keywords: Elior, Rachel; Dead Sea scrolls; Apocalyptic literature -- History and criticism; Jewish magic; Mysticism -- Judaism; Messianism; Festschriften; Bible. -- Criticism, interpretation, etc; Rabbinical literature -- History and criticism; Electronic books; RELIGION / Biblical Studies